2006
DOI: 10.1159/000092518
|View full text |Cite
|
Sign up to set email alerts
|

BAY 41-2272, a Direct Activator of Soluble Guanylate Cyclase, Reduces Right Ventricular Hypertrophy and Prevents Pulmonary Vascular Remodeling during Chronic Hypoxia in Neonatal Rats

Abstract: Exposure to hypoxia during the first weeks of life in newborn rats decreases vascular growth and alveolarization and causes pulmonary hypertension (PH). BAY 41-2272 is a novel direct activator of soluble guanylate cyclase independent of nitric oxide, effective as an acute pulmonary vasodilator in an animal model of persistent pulmonary hypertension of the newborn, but whether prolonged BAY 41-2272 therapy is effective in the setting of chronic PH is unknown. We hypothesize that BAY 41-2272 would prevent PH ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
37
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 64 publications
(54 reference statements)
5
37
0
1
Order By: Relevance
“…Chronic hypoxia can impair pulmonary vascularization and alveolar formation in neonatal rats and humans (14,15). Alveolar hypoxia in this model reduced pulmonary vessel density, RAC and increased mean Lm.…”
Section: Discussionmentioning
confidence: 75%
“…Chronic hypoxia can impair pulmonary vascularization and alveolar formation in neonatal rats and humans (14,15). Alveolar hypoxia in this model reduced pulmonary vessel density, RAC and increased mean Lm.…”
Section: Discussionmentioning
confidence: 75%
“…The former sGC stimulator BAY 41-2272 has demonstrated similar efficacy in experimental PAH induced by hypoxia in mice [12] and hypoxia in neonatal rats [45]. Acute vasoreactivity testing revealed a strong reduction in pulmonary vascular resistance which was shown in different species, such as mice [12] or sheep [11,46], which indicates strong biological relevance of sGC in regulating pulmonary vascular tone.…”
Section: Discussionmentioning
confidence: 87%
“…BAY 41-2272 is closely related to BAY 41-8543, and this sGC stimulator has been shown to have significant pulmonary vasodilator activity in a variety of species (9,10,13,15,34,37). BAY 41-2272 has been shown to reduce right ventricular hypertrophy and pulmonary vascular remodeling in a chronic hypoxia-induced model of pulmonary hypertension (8). It has been reported that, when either BAY 41-2272 or BAY 41-8543 was administered by inhalation to awake lambs, the pyrazolopyridine compounds had selective pulmonary vasodilator activity, and BAY 41-8543 could enhance the magnitude and prolong the duration of the vasodilator response to inhaled NO (9,13).…”
mentioning
confidence: 99%